EVALUASI JALAN LAYANG NON TOL PAKET CASABLANCA KUNINGAN-JAKARTA - Alan Elang Filtrana; Ester Melina; Sri Tudjono; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Separated Highway Casablanca Package is located at Kuningan, Jakarta. This separated highways is designed using prestressed concrete box girder construction. The erection method is conducted by means of balance cantilever method. The main equipment used in the erection of box girder is launcher gantry. Total length of the separated highways is 1175 m, which is divided into 24 spans. This separated highways has 25 piers. The first step of designing this separated highway is by designing the dimension of the box girder. The next step is analyzing the loads that are predicted to work on the structure, namely load, traffic load, wind load, and earthquake load. Next, structural analysis is carried out to obtain the internal forces and stresses in the structure. The result of the structural analysis is used to calculate loss of prestressing force, needs of tendon, and the reinforcement of box girder. The next step is designing Piers and Foundation. The reinforcement in the piers is 1,33 times of the minimum reinforcement required by analysis. The Foundation uses bore piles and calculated using Broms method.